Van Halen, brown M&M's, and quality control - Venkataraman, Ray R.; Pinto, Jeffrey K. (Los Angeles, CA : SAGE Publications, Inc., 2017)
This case describes how the rock band, Van Halen, used the presence of brown M&Ms in the backstage area as a visible signal to quality lapses of conformance to its performance specifications.
Originally published in Venkataraman, R. R., & Pinto, J. K. (2017). Van Halen, brown M&M's and quality control. In Operations management: Managing global supply chains( pp. 191). Thousand Oaks, CA: SAGE Publications. ISBN: 9781506302935.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Van Halen (Musical group); Quality control